Ferromagnetism: Self‐Assembled Platinum Nanochain Networks Driven by Induced Magnetic Dipoles (Adv. Funct. Mater. 7/2014). (February 2014) - Gao, Min‐Rui; Zhang, Shi‐Ran; Xu, Yun‐Fei; Zheng, Ya‐Rong; Jiang, Jun; Yu, Shu‐Hong
<x xml:space="preserve">Abstract</x> Unique chain‐like networks of platinum (Pt) nanocrystals can be self‐organized spontaneously in a polyol solution. On page 916, S. H. Yu and co‐workers find that in situ‐formed magnetic dipoles originating from the alterant Pt electronic structure and modified by the capped polyvinylpyrrolidone (PVP) molecules are found to be the driving force of this self‐assembled structures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>